Bacteriological Contamination of Groundwater Affected by Septic Tanks Condition in Koto Tangah District, Padang, Indonesia - Dewi Yusnisa Putri; Shinta Indah; Denny Helard (Universitas Airlangga, 2022)
Introduction: Padang City Sanitation Working Group reported that 34.32% of households in Padang City use unsafe latrines with septic tanks that still do not meet the standards which potentially causes the wastewater from the septic tanks to contaminate the water of the wells. This study was conducted to analyse the effects of the septic tank condition on the microbiological quality parameters of the well-water, namely total coliform and Escherichia coli in Koto Tengah District, Padang. Methods: This study uses a quantitative research method. The data were collected by questionnaires, observation, interviews, and laboratory tests. Water sampling was collected by using the purposive sampling method where the water is taken from 20 wells originating from 10 coastal and 10 non-coastal areas. Results and Discussion: Total coliform was found in all samples, while Escherichia coli was found in two samples from coastal and five from non-coastal regions. The septic tank condition had a strong correlation with the total coliform concentration (r= -0.531) and affected the total coliform concentration in the well-water by 30.8%. However, the Escherichia coli concentration was not related and not affected by the condition of the septic tank (p>0.05). There was no significant difference in the concentration of the microbiological parameters in the coastal and non-coastal areas. Conclusion: The microbiological quality of the well-water did not comply with the quality standards to be used as water sources for the community. The total coliform concentration in the well-water was shown to have a close relationship with the septic tank's condition.